Baseline haemoglobin A1c and the risk of COVID‐19 hospitalization among patients with diabetes in the INSIGHT Clinical Research Network. Issue 5 (28th February 2022) - Min, Jea Young; Williams, Nicholas; Simmons, Will; Banerjee, Samprit; Wang, Fei; Zhang, Yongkang; Reese, April B.; Mushlin, Alvin I.; Flory, James H.
Abstract: Aims: To examine the association between baseline glucose control and risk of COVID‐19 hospitalization and in‐hospital death among patients with diabetes. Methods: We performed a retrospective cohort study of adult patients in the INSIGHT Clinical Research Network with a diabetes diagnosis and haemoglobin A1c (HbA1c) measurement in the year prior to an index date of March 15, 2020. Patients were divided into four exposure groups based on their most recent HbA1c measurement (in mmol/mol): 39–46 (5.7%–6.4%), 48–57 (6.5%–7.4%), 58–85 (7.5%–9.9%), and ≥86 (10%). Time to COVID‐19 hospitalization was compared in the four groups in a propensity score‐weighted Cox proportional hazards model adjusting for potential confounders. Patients were followed until June 15, 2020. In‐hospital death was examined as a secondary outcome. Results: Of 168, 803 patients who met inclusion criteria; 50, 016 patients had baseline HbA1c 39–46 (5.7%–6.4%); 54, 729 had HbA1c 48–57 (6.5–7.4%); 47, 640 had HbA1c 58–85 (7.5^%–9.9%) and 16, 418 had HbA1c ≥86 (10%). Compared with patients with HbA1c 48–57 (6.5%–7.4%), the risk of hospitalization was incrementally greater for those with HbA1c 58–85 (7.5%–9.9%) (adjusted hazard ratio [aHR] 1.19, 95% confidence interval [CI] 1.06–1.34) and HbA1c ≥86 (10%) (aHR 1.40, 95% CI 1.19–1.64). The risk of COVID‐19 in‐hospital death was increased only in patients with HbA1c 58–85 (7.5%–9.9%) (aHR 1.29, 95% CI 1.06, 1.61). Conclusions: Diabetes patients with high baseline HbA1c had a greater risk of COVID‐19 hospitalization, although association between HbA1c and in‐hospital death was less consistent. Preventive efforts for COVID‐19 should be focused on diabetes patients with poor glucose control.